Analisis Pengembangan Sistem Informasi Manajemen Fiber To The Home Menggunakan Metode Pieces Pada PT. XYZ - Yazid Khairul Rizal; Samsudin Samsudin (Jurnal Informatika, 2024)
PT. XYZ is a company engaged in the field of digital information technology and telecommunications services in Indonesia, utilizing Fiber To The Home (FTTH) technology as a telecommunications solution to connect service providers with residential customers. PT.XYZ faces challenges in managing FTTH data due to the manual recording of information in books, which can lead to inaccuracies, hinder data accessibility, and complicate the understanding of network transmission point distribution. A viable approach to address this issue is the implementation of a management information system capable of managing FTTH data and visualizing the distribution of transmission points based on current data. This project aims to create a web-based FTTH management information system to enhance the efficiency of fiber optic network data management at PT.XYZ. This research employs the PIECES technique (Performance, Information, Economy, Control, Efficiency, Service) for requirements analysis and system assessment. The system is built using the Waterfall methodology, which includes phases of requirements analysis, design, implementation, and testing. The results of black-box testing indicate that all scenarios effectively meet the specified requirements. Usability testing using the PIECES framework shows that the average user satisfaction falls within the "Satisfied" category across all criteria. This system offers a more effective and organized FTTH data management solution, capable of visualizing the distribution of network transmission points, thereby assisting operators in their daily operations.